Examining networked NGO services: reconceptualising value co-creation. Issue 7 (6th June 2018) - Best, Bernadette; Moffett, Sandra; Hannibal, Claire; McAdam, Rodney
Abstract : Purpose: The purpose of this paper is to explain how value is co-created in a many-to-many (MTM) context. The authors use a case study of a non-governmental service delivery consortium engaging multiple actors to examine how value is co-created beyond the buyer-supplier dyad. Design/methodology/approach: An explanatory case study of a consortium of seven UK non-governmental organisations (NGOs) delivering public service contracts is presented. Multiple data collection methods are combined; semi-structured interviews ( n =30) and focus groups with internal stakeholders ( n =5), participant observations ( n =4) and document analysis. Findings: The authors use three illustrative empirical examples to show how different sources, types, enablers and mechanisms of VCC are evident during service provision activities. The findings show how different service provision activities utilise different dimensions, leading the authors to suggest that dimensions of VCC may be context dependent. Research limitations/implications: As consortia differ in their context and function, the findings may not be generalisable. Nevertheless, they provide specific examples of sources, types, enablers and mechanisms of value co-creation (VCC) that may be applicable to private, public and NGOs. Practical implications: Understanding how value is co-created with multiple stakeholders can offer competitive advantages likely to lead to improved sustainability, impact and performance. Originality/value: The empirical study offers a reconceptualisation of VCC in a MTM context. The paper combines disparate perspectives of VCC to offer a more holistic perspective.